Differences in the efficacy of carboxylic acid amide fungicides against less sensitive strains of Plasmopara viticola. Issue 8 (30th November 2015) - Nanni, Irene Maja; Pirondi, Alessandro; Mancini, Daniela; Stammler, Gerd; Gold, Randall; Ferri, Ilaria; Brunelli, Agostino; Collina, Marina
Abstract: BACKGROUND: Plasmopara viticola is controlled by fungicides with different modes of action, including carboxylic acid amides (CAAs). The aim of this study was to evaluate differences in the response of CAA‐resistant P. viticola strains towards CAAs. RESULTS: The G1105S mutation affects all four CAAs, but with different impacts. While this confirms that they have the same mode of action, it shows that differences between CAAs can occur. CONCLUSION: Further molecular modelling and docking studies are needed to gain a better understanding of the different behaviours reported here. © 2015 Society of Chemical Industry